2021
DOI: 10.2147/rru.s306467
|View full text |Cite
|
Sign up to set email alerts
|

Incidence and Predictors of Acute Kidney Injury Among Newly Diagnosed Type 2 Diabetes Patients at Chronic Follow-Up Clinic of University of Gondar Comprehensive Specialized Hospital: A Retrospective Follow-Up Study

Abstract: Background: Acute kidney injury is a common disorder worldwide, occurring in more than 13 million per year, 85% of whom live in developing countries. The high incidence of acute kidney injury among type 2 diabetic patients is a major cause of morbidity and mortality. There is limited data that address the incidence and predictors of acute kidney injury to apply evidence-based interventions in developing countries including Ethiopia specifically in the study area. Methods: Institution-based retrospective follow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 27 publications
2
9
0
Order By: Relevance
“…In China, a country with a large DM patient population, a national survey indicated that diabetic status was positively associated with the length of stay and hospital expenditure after adjusting for possible confounders 53 . In comparison, in fast‐growing economies, such as Ethiopia, 19.76% (95% CI; 16.2–23.8) of the study population (420 DM patients) developed AKI, with a median follow‐up period of 30.75 months 40 . In addition, blacks with DM had 50% higher age‐ and sex‐adjusted AKI odds than whites with DM (odds ratio [OR]: 1.51; 95% CI 1.37–1.66).…”
Section: The Global Atlas Of Aki In Dm: Mapping the Way Forward In Ad...mentioning
confidence: 99%
See 1 more Smart Citation
“…In China, a country with a large DM patient population, a national survey indicated that diabetic status was positively associated with the length of stay and hospital expenditure after adjusting for possible confounders 53 . In comparison, in fast‐growing economies, such as Ethiopia, 19.76% (95% CI; 16.2–23.8) of the study population (420 DM patients) developed AKI, with a median follow‐up period of 30.75 months 40 . In addition, blacks with DM had 50% higher age‐ and sex‐adjusted AKI odds than whites with DM (odds ratio [OR]: 1.51; 95% CI 1.37–1.66).…”
Section: The Global Atlas Of Aki In Dm: Mapping the Way Forward In Ad...mentioning
confidence: 99%
“…53 In comparison, in fast-growing economies, such as Ethiopia, 19.76% (95% CI; 16.2-23.8) of the study population (420 DM patients) developed AKI, with a median follow-up period of 30.75 months. 40 In addition, blacks with DM had 50% higher age-and sex-adjusted AKI odds than whites with DM (odds ratio [OR]: 1.51; 95% CI 1.37-1.66). There was no racial difference in length of stay or in-hospital mortality among AKI cases.…”
Section: Global Epidemiology Of Aki In Dmmentioning
confidence: 99%
“…University of Gondar Comprehensive Specialized Hospital is located in Gondar Town, which is the capital city central Gondar zone. It is 738 kilometers from Addis Ababa and 173 kilometers from Bahir Dar [14]. These hospitals currently have 51 adult ICU beds that are working and providing services to critically ill patients.…”
Section: Study Settingmentioning
confidence: 99%
“…The average AKI incidence was 33.4% in developed nations and 37.7% in developing countries [5]. Studies conducted in Africa showed that the incidence of AKI ranges from 11% to 58.5% [6-12] and 14.5% to 17.76% in Ethiopia among Diabetic patients [13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…As in developed countries, the major risk factors for AKI in SSA are comorbidities such as diabetes mellitus, hypertension, cardiovascular disease, and obesity, which are a corollary of the progressive westernisation of SSA society [ 32 34 , 44 46 ]. As Olowu et al point out, the rapid urbanisation of SSA combined with an increase in the prevalence of these non-infectious comorbidities have significantly influenced the clinical features of AKI [ 8 ].…”
Section: Factors Associated With Aki In Sub-saharan Africamentioning
confidence: 99%